1991
DOI: 10.1111/j.1468-2958.1991.tb00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Marital Satisfaction and Couple Type as Functions of Relational Expectations

Abstract: The present study examined the role played by relational expectations in determining marital satisfaction and in discriminating between married couple types. The discrep ancy between one's expectations for his or her spouse's relntiorral behavior and one's perceptions of his or her spouse's actual behavior significantly predicted marital sutisfaction. Discrepancy scoresfor the relational dimensions of intimacy, distance, equality/ trust, dominance, and noncomposurelarousal appear to be most central in predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 37 publications
4
50
2
Order By: Relevance
“…At least within the context of social interaction, it appears that dominance is a less complex concept than affiliation. 5 Similar to our findings, several other studies have found that dominance and equality were perceived as distinct constructs (Burgoon & Hale, 1987, Study 3;Kelley & Burgoon, 1991 ;Walther & Burgoon, 1992). Notably, equality is not viewed as the midpoint on a dominance-submissiveness continuum.…”
Section: The Nature Of Affiliationsupporting
confidence: 91%
“…At least within the context of social interaction, it appears that dominance is a less complex concept than affiliation. 5 Similar to our findings, several other studies have found that dominance and equality were perceived as distinct constructs (Burgoon & Hale, 1987, Study 3;Kelley & Burgoon, 1991 ;Walther & Burgoon, 1992). Notably, equality is not viewed as the midpoint on a dominance-submissiveness continuum.…”
Section: The Nature Of Affiliationsupporting
confidence: 91%
“…For example, Kelley and Burgoon (1991) reported that whether the spouse's behaviors met with one's marital expectations was a stronger predictor of marital satisfaction than the agreement between spouses. Moreover, different relationship expectations were found to affect relationship quality with varying strength.…”
Section: Dynamic Marital Goals and Marital Satisfactionmentioning
confidence: 95%
“…In terms of expectations, communicators assess deviations from what they expect during an interaction, and under certain conditions these violations lead to negative outcomes. For example, Kelly and Burgoon (1991) documented that unmet expectations for intimacy in married couples correspond with reduced satisfaction. Along these lines, we contend that unmet expectations for support also lead to detrimental outcomes.…”
Section: Support Gaps Race and Outcomesmentioning
confidence: 99%